Ivan Franko about the nature and functionality of religion - Anatolii M. Kolodnyi (Українське Pелігієзнавство, 2016)
Recognizing free-thinking with atheism, we often do not recognize the existence of religious free-thinking. The fact is that the Church somehow perceive freedom of religion, freedom of religion, but each of them does not allow itself freedom In religion, freedom In its religion. Any deviation from the dogmas or canons, the arbitrary interpretation of certain provisions of the doctrine, and especially the anti-clericalism, is perceived as heresy, and ultimately qualifies as atheism. That is why Ivan Franko was uncomfortable with the church leadership of the Greek Catholics of Galicia, and the Orthodox enjoyed his works, where he criticized the Vatican, his policy on Slavs. About the work of the thinker, in which they considered worldview problems, did not even speak. Ivan Franko (1856 - 1916) is an epoch-making figure in the history of Ukrainian spirituality. That is why he was tried and tried to enroll in his assets followers of different ideological orientations. He is a materialist and pantheist, an atheist and believer, a dialectic and metaphysician, a Marxist and an anti-Marxist, an internationalist and a nationalist